Carbon Markets, Institutions, Policies, and Research - Larson, Donald F. (World Bank, Washington, DC, 2012)
The scale of investment needed to slow greenhouse gas emissions is larger than governments can manage through transfers. Therefore, climate change policies rely heavily on markets and private capital. This is especially true in the case of the Kyoto Protocol with its provisions for trade and investment in joint projects. This paper describes institutions and policies important for new carbon markets and explains their origins. Research efforts that explore conceptual aspects of current policy are surveyed along with empirical studies that make predictions about how carbon markets will work and perform. The authors summarize early investment and price outcomes from newly formed markets and point out areas where markets have preformed as predicted and areas where markets remain incomplete. Overall the scale of carbon-market investment planned exceeds earlier expectations, but the geographic dispersion of investment is uneven and important opportunities for abatement remain untapped in some sectors, indicating a need for additional research on how investment markets work. How best to promote the development and deployment of new technologies is another promising area for study identified in the paper.